2016
DOI: 10.1111/febs.13944
|View full text |Cite
|
Sign up to set email alerts
|

Mature neurons dynamically restrict apoptosis via redundant premitochondrial brakes

Abstract: Apoptotic cell death is critical for the early development of the nervous system, but once the nervous system is established, the apoptotic pathway becomes highly restricted in mature neurons. However, the mechanisms underlying this increased resistance to apoptosis in these mature neurons are not completely understood. We have previously found that members of the miR-29 family of microRNAs (miRNAs) are induced with neuronal maturation and that overexpression of miR-29 was sufficient to restrict apoptosis in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…105 On the other hand, regarding other miRNAs here identified, such as miR-221-3p, miR-222-3p, miR-24-3p, and miR-28-5p, limited or conflicting data about their function and implication in neuronal processes have been reported. [106][107][108][109] Besides neurotrophin signaling, interestingly, the pathway-based analysis revealed that these miRNAs act on pathways known to be altered in ischemic conditions and involved in neuroprotection, such as TNF, Hippo, and PI3K. [110][111][112] Among the miRNAs targets here identified, supposed to be downregulated in our model, we highlighted several genes involved in apoptosis and inflammation processes.…”
Section: Discussionmentioning
confidence: 99%
“…105 On the other hand, regarding other miRNAs here identified, such as miR-221-3p, miR-222-3p, miR-24-3p, and miR-28-5p, limited or conflicting data about their function and implication in neuronal processes have been reported. [106][107][108][109] Besides neurotrophin signaling, interestingly, the pathway-based analysis revealed that these miRNAs act on pathways known to be altered in ischemic conditions and involved in neuroprotection, such as TNF, Hippo, and PI3K. [110][111][112] Among the miRNAs targets here identified, supposed to be downregulated in our model, we highlighted several genes involved in apoptosis and inflammation processes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the downregulation of miR-29 contributed to neuronal cell death in focal ischemia by enhancing the expression of Bcl-2-like protein 2, an anti-apoptotic member of the BCL-2 protein family ( 31 ). By contrast, upregulation of miR-29 protected neurons from apoptosis during neuronal maturation ( 32 ), a well as during forebrain ( 24 ) and focal ischemia ( 26 ). Therefore, the expression and function of miR-29b in cerebral ischemia injury remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, miR-29b is also significantly up-regulated in neural cells under an OGD/R environment and in patients with cerebral I/R injury ( 10 , 15 ). Activated miR-29b has also been reported to promote neural cell apoptosis targeting BH3 protein during neuronal maturation ( 16 ). Supporting previous studies, our results indicate that miR-29 binds the 3′UTR of MCL-1, an important Bcl-2 family protein.…”
Section: Discussionmentioning
confidence: 99%